PENGAWETAN KAYU KARET,AGATHIS, DAN TUSAM DENGAN METODE TEKANAN BERGANTI - Barly Barly; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The paper deals with an experiment of alternating pressure method on three wood species with borax. The green wood samples were impregnated with three percent borax solution. The results of experiment are as follows :1. Wood species and treatment schedule show non significant effect on boron penetration and retention.2. In general the impregnation of the green wood results in variable treatment and limited penetration and retention.3. Retention and penetration showed better figures when only modifying the treating cycle rather than using a pretreatment.